1996
DOI: 10.1099/0022-1317-77-5-919
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of the human polyomavirus JC virus types A and B and isolation of a new type from Ghana

Abstract: The JC polyomavirus (JCV) is ubiquitous in humans, infecting children asymptomatically, then persisting in renal tissue. Since JCV DNA can be readily isolated from urine, it should be a useful tool with which to study the evolution of DNA viruses in humans. We showed that JCV DNA from the urine of Japanese, Taiwanese, Dutch and German patients can be classified into A and B types, based upon restriction fragment length polymorphisms (RFLPs). This work was extended in the present study. We established multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
3

Year Published

1997
1997
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 30 publications
3
65
0
3
Order By: Relevance
“…This was later identified as a new subtype of JCV when similar strains were sequenced from the urine of Africans from Ghana (Guo et al 1996). Type 6 strains have also been sequenced from the brains of AIDS patients with PML from the Ivory Coast (Stoner et al 1998b) as well as the urine of an immunocompetent individual from Sierra Leone (Chima, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was later identified as a new subtype of JCV when similar strains were sequenced from the urine of Africans from Ghana (Guo et al 1996). Type 6 strains have also been sequenced from the brains of AIDS patients with PML from the Ivory Coast (Stoner et al 1998b) as well as the urine of an immunocompetent individual from Sierra Leone (Chima, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize that the two African genotypes of JCV (Types 3 and 6) may have coevolved, independently of each other, in their respective African hosts. All genotype studies on JCV in Africans so far have shown that both Type 3 and 6 strains can be found in West and Central Africa (Guo et al 1996, Sugimoto et al 1997, Stoner et al 1998b, while Type 3 is the only genotype so far described from East Africa (Agostini et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis of SC isolates worldwide based on complete viral DNA sequences We sequenced 15 complete JCV (SC) DNA clones, including seven established previously (Guo et al, 1996) and eight established in this study (the origins of these clones are shown in Table 1 and Figure 1). An NJ phylogenetic tree was constructed from these sequences and 50 complete SC sequences reported previously (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Using molecular cloning (see below), eight JCPyV isolates (UR-8, Han-1, -3 and -4, RH-2 and -5, and MU-4 and -7) were recovered in the current study, and seven isolates (C1, CW-7 and -11, ID-2, ML-2 and -4, and ZA-3) were obtained in a previous study (Guo et al, 1996), using urine samples collected from indigenous volunteers or patients aged 40 years or older at the sites indicated in Table 1 and Figure 1. The origins of the JCPyV isolates used in this study whose complete JCPyV sequences have been reported previously are also shown in Table 1 and Figure 1.…”
Section: Geographic Origins Of Jcpyv Isolatesmentioning
confidence: 99%
See 1 more Smart Citation